KEUNGGULAN KOMPETITIF PADI SAWAH VARIETAS LOKAL DI SUMATERA BARAT - Nurnayetti ,; Atman ; (Balai Besar Pengkajian dan Pengembangan Teknologi Pertanian, 2013)
ABSTRACTThe Strength Competitiveness of Local Lowland Rice Variety in West Sumatera. The assessment needs to be done to determine the causes of farmers preference in choosing local varieties. The purpose of the assessment is to examine the strength competitiveness of local varieties than national varieties from social economic aspects, to be used as a development strategy of national superior variety. Research done on 2012 in the Pesisir Selatan, Padang Pariaman and Agam Districts. The information obtained with surveys ways to 60 respondents each location. Data was analyzed as descriptive and cross tabulation ways. The assessment results concluded that competitiveness of lokal varieties is higher than superior varieties, seen from the higher location distribution of local varieties (62.2%) than superior varieties (37.8%), utilization of local varieties (76%) is higher than superior varieties (24%), and more than 50% farmers tend to use local varieties. The reason people still survive using local varieties primarily because of